2018
DOI: 10.1007/s11748-018-1010-2
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of sternal closure with bioresorbable plate in respiratory function after coronary artery bypass grafting

Abstract: Sternal fixation with bioresorbable plate could reduce impairment of postoperative respiratory function in comparison to wire cerclage only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Sternum immobilisation after median sternotomy is a critical procedure after cardiac surgery 17 . Traditional stainless steel wire cerclage for immobilisation can cause the sternum dehiscence due to the cutting action of metal wires, and can hardly provide good sternal stability leading to serious complications such as pain, osteomyelitis and even respiratory complications 18,19 . In addition, residual undegradable steel wires may lead to future problems such as chronic bone non-union and deep sternal wound infection 20,21 .…”
mentioning
confidence: 99%
“…Sternum immobilisation after median sternotomy is a critical procedure after cardiac surgery 17 . Traditional stainless steel wire cerclage for immobilisation can cause the sternum dehiscence due to the cutting action of metal wires, and can hardly provide good sternal stability leading to serious complications such as pain, osteomyelitis and even respiratory complications 18,19 . In addition, residual undegradable steel wires may lead to future problems such as chronic bone non-union and deep sternal wound infection 20,21 .…”
mentioning
confidence: 99%
“…Sakashita et al con rmed that xation sternotomy with Super FIXSORB MX40 mesh plates promoted bone stability and decreased postsurgical pain [13]. Additionally, Tamura et al reported that xation with Super FIXSORB MX40 mesh plates resulted in increased sternal stability, decreased postoperative pain, and improved postoperative respiratory function [9]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mesh plate is resorbed after approximately 6 years through osteoconduction [5] and has already been used for xing rib fractures and ail chest repair [6,7]. Furthermore, postoperative respiratory conditions are more stable when a mesh plate is used for median sternotomy after congenital cardiac surgery and coronary artery bypass grafting [8,9]. Therefore, we devised a method to close the sternum by external xation using a three-piece mesh plate (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The main issue when introducing new materials in surgery is to verify safety. Absorbable long-lasting sutures, commonly used in general surgery, 1 have typically only been utilized in cardiovascular surgery for sternal closure after pediatric and adult cardiac surgery procedures, [2][3][4][5] for vascular surgery procedures, [6][7][8][9][10] for diaphragmatic or superficial cutaneous sutures related to cardiovascular procedures, 11,12 and for experimental research surgery in animals. 13 Despite being regularly used in hospitals in Europe as purse strings for arterial and venous cannulation for cardiopulmonary bypass in pediatric heart surgery, to the best of our knowledge, their use in this specific utilization has not been reported.…”
Section: Discussionmentioning
confidence: 99%